2017
DOI: 10.21037/atm.2017.06.04
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with poorer range of motion and Tegner scores following hamstring autograft anterior cruciate ligament reconstruction in Asians

Abstract: Obese patients had poorer range of motion and Tegner scores as compared to their nonobese counterparts following primary ACLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…All investigations were available in electronic databases between 2010 and 2021. Out of 10 observational studies, there were 7 cohort [ [34] , [35] , [36] , [37] , [38] , [39] , 40 ] and 3 cross-sectional [ [41] , [42] , [43] ] research. In terms of the level of evidence, one study reported level I [ 35 ], 5 investigations level II [ 36 , 38 , 39 , 42 , 40 ], and 4 articles level III [ 34 , 37 , 41 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All investigations were available in electronic databases between 2010 and 2021. Out of 10 observational studies, there were 7 cohort [ [34] , [35] , [36] , [37] , [38] , [39] , 40 ] and 3 cross-sectional [ [41] , [42] , [43] ] research. In terms of the level of evidence, one study reported level I [ 35 ], 5 investigations level II [ 36 , 38 , 39 , 42 , 40 ], and 4 articles level III [ 34 , 37 , 41 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of 10 observational studies, there were 7 cohort [ [34] , [35] , [36] , [37] , [38] , [39] , 40 ] and 3 cross-sectional [ [41] , [42] , [43] ] research. In terms of the level of evidence, one study reported level I [ 35 ], 5 investigations level II [ 36 , 38 , 39 , 42 , 40 ], and 4 articles level III [ 34 , 37 , 41 , 43 ]. Furthermore, 7171 individuals with a history of ACLR participated in studies that were involved in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Several studies that have examined soft tissue injuries of the knee have shown the negative impact of obesity on ROM, which is consistent with the findings of this study. 6 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…21 Several studies that have examined soft tissue injuries of the knee have shown the negative impact of obesity on ROM, which is consistent with the findings of this study. 6,19 Smoking has been implicated widely across medicine as associated with poor wound healing and an array of pathology. The documented effects of byproduct toxic compounds found within cigarette smoke-such as nicotine, carbon monoxide, and hydrogen cyanide-suggest possible mechanisms for impaired wound healing.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%